الاسباب التكنولوجية للطالق: تحليل قانوني للتحديات والتغيرات الاجتماعية - بوصالح باسم - بن يحي حسينة (جامعة المسيلة, 2024)
This study aims to understand electronic divorce introduced by technological developments which affect all the aspects of life, including family, whereby divorce form is sent and received, with its provisions and effects, through technological means. It also aims to present the technological causes leading to divorce, the most important of which is online marital infidelity and the use of social media platforms as modern causes of divorce, and it elucidates the legal and legislative rulings regarding these causes and their impacts on the family and the society. We have used in our study the descriptive, analytical and comparative methods to reveal the elements of the subject of study in order to demonstrate its intricacies and consequences. The study has reached many findings, including that; - It is valid to consider the electronic divorce as a juridical alternative to ordinary divorce in light of technological development. - Proving electronic divorce using technological means is difficult
Keywords: : family; electronic divorce; online marital infidelity; social media platforms